Proceedings of the First International Conference on Intelligent Computing and Communication - Mandal, Jyotsna Kumar; Satapathy, Suresh Chandra; Sanyal, Manas Kumar; Bhateja, Vikrant; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
The book covers a wide range of topics in Computer Science and Information Technology including swarm intelligence, artificial intelligence, evolutionary algorithms, and bio-inspired algorithms. It is a collection of papers presented at the First International Conference on Intelligent Computing and Communication (ICIC2) 2016. The prime areas of the conference are Intelligent Computing, Intelligent Communication, Bio-informatics, Geo-informatics, Algorithm, Graphics and Image Processing, Graph Labeling, Web Security, Privacy and e-Commerce, Computational Geometry, Service Orient Architecture, and Data Engineering.
Section 1. Biomedical Image Processing and Bioinformatics -- Section 2. Cloud Computing -- Section 3. Communication Network and Services -- Section 4. Data Analytics and Data Mining -- Section 5. Device System and Modeling -- Section 6. Image Processing and Pattern Recognition -- Section 7. Security and Cryptography -- Section 8. Wireless Sensor Network. .
Keywords: Computational intelligence; Telecommunication; Artificial intelligence; Data protection; Computational Intelligence; Communications Engineering, Networks; Artificial Intelligence; Data and Information Security